TEOLOGI SPIRITUALITAS IMAMAT Tinjauan Penghayatan Penderitaan - M.T. Eleine Magdalena (Studia Philosophica et Theologica, 2005)
Spirituality of priesthood is so rich. It flows from Christ as the Priest himself. One side of priestly life is living out the suffering of Christ. Jesus Christ redeemed the world by his suffering on the cross, so does a priest; he is the witness of the redemption of Christ through perseverance to live his suffering. In this article I shall explore concrete experience of suffering of the priestly life from spiritual point of view. I regard that in priestly life suffer means love. To be perseverant in suffering means to be faithful in love toward God and people. Nothing worth for priest is but to serve God and his people. To serve means to suffer. Understanding of priestly life suggests that suffering does not designate something to avoid. Instead, suffering is the spiritual way toward promotion of redemption. Priestly life is worthwhile and choice worthy simply because it leads daily experience of suffering to salvation.